Acute Flaccid Myelitis: A Multidisciplinary Protocol to Optimize Diagnosis and Evaluation. (May 2021) - Vawter-Lee, Marissa; Peariso, Katrina; Frey, Mary; Bolikal, Priya; Schaffzin, Joshua K.; Schwentker, Ann; O'Brien, William T.; Zamor, Ronine; Kerrey, Benjamin T.
Acute flaccid myelitis is an emerging neurologic disease, first described in 2014 and predominantly affecting young children. Acute flaccid myelitis cases tend to spike every 2 years, in the late summer to fall, and the next peak is expected in 2020. The diagnosis of acute flaccid myelitis is often delayed, leading to suboptimal evaluation, including incomplete laboratory assessment. Acute and chronic morbidity are high, and a standardized, multidisciplinary approach to evaluation and treatment is essential to optimizing outcomes. In a review of acute flaccid myelitis patients treated in 2018 at our institution, we noted considerable variability in days to presentation, evaluation, and treatment. In response, the authors developed a protocol for the evaluation and management of pediatric patients suspected of having acute flaccid myelitis. The protocol was developed using local experience/case review, expert consensus, and the relevant literature. The protocol spans the spectrum of care, from initial evaluation in a primary care or emergency setting, to acute hospital management and evaluation and long-term inpatient and rehabilitation settings. The purpose of this report is both to share the findings from our 2018 case review and to disseminate our acute flaccid myelitis protocol. Our hope is that publication of our protocol will both inform the development of a standardized approach to acute flaccid myelitis and to encourage other centers to form a multidisciplinary acute flaccid myelitis team to provide expert care throughout the disease process, from presentation to recovery.